Software engineering trends and techniques in intelligent systems : proceedings of the 6th Computer Science On-line Conference 2017 (CSOC2017). Vol 3 - Šilhavý, Radek; Šilhavý, Petr; Prokopová, Zdeňka; Šenkeřík, Roman; Oplatková, Zuzana (Springer, 2017)
This book presents new approaches and methods to solve real-world problems as well as exploratory research describing novel approaches in the field of software engineering and intelligent systems. It particularly focuses on modern trends in selected fields of interest, introducing new algorithms, methods and application of intelligent systems in software engineering. The book constitutes the refereed proceedings of the Software Engineering Trends and Techniques in Intelligent Systems Section of the 6th Computer Science On-line Conference 2017 (CSOC 2017), held in April 2017.
Keywords: Software engineering -- Congresses.; Artificial intelligence -- Congresses.; elektronické knihy; electronic books